Development of a Fluorescent Reporter System to Delineate Cancer Stem Cells in Triple-Negative Breast Cancer. (15th May 2015) - Thiagarajan, Praveena S.; Hitomi, Masahiro; Hale, James S.; Alvarado, Alvaro G.; Otvos, Balint; Sinyuk, Maksim; Stoltz, Kevin; Wiechert, Andrew; Mulkearns-Hubert, Erin; Jarrar, Awad M.; Zheng, Qiao; Thomas, Dustin; et al.
Abstract: Advanced cancers display cellular heterogeneity driven by self-renewing, tumorigenic cancer stem cells (CSCs). The use of cell lines to model CSCs is challenging due to the difficulty of identifying and isolating cell populations that possess differences in self-renewal and tumor initiation. To overcome these barriers in triple-negative breast cancer (TNBC), we developed a CSC system using a green fluorescent protein (GFP) reporter for the promoter of the well-established pluripotency gene NANOG . NANOG-GFP+ cells gave rise to both GFP+ and GFP − cells, and GFP+ cells possessed increased levels of the embryonic stem cell transcription factors NANOG, SOX2, and OCT4 and elevated self-renewal and tumor initiation capacities. GFP+ cells also expressed mesenchymal markers and demonstrated increased invasion. Compared with the well-established CSC markers CD24 − /CD44 +, CD49f, and aldehyde dehydrogenase (ALDH) activity, our NANOG-GFP reporter system demonstrated increased enrichment for CSCs. To explore the utility of this system as a screening platform, we performed a flow cytometry screen that confirmed increased CSC marker expression in the GFP+ population and identified new cell surface markers elevated in TNBC CSCs, including junctional adhesion molecule-A (JAM-A). JAM-A was highly expressed in GFP+ cells and patient-derived xenograft ALDH+ CSCs compared with the GFP − and ALDH − cells, respectively. Depletion of JAM-A compromised self-renewal, whereas JAM-A overexpression induced self-renewal in GFP − cells. Our data indicate that we have defined and developed a robust system to monitor differences between CSCs and non-CSCs in TNBC that can be used to identify CSC-specific targets for the development of future therapeutic strategies. Stem Cells. Stem Cells 2015;33:2114–2125